ANALISIS YURIDIS KEDUDUKAN KANTOR PELAYANAN PAJAK PRATAMA MEDAN BELAWAN SEBAGAI KREDITUR PREFEREN DALAM PELUNASAN UTANG PAJAK PT. INDUSTRIES BADJA GARUDA (STUDI TERHADAP PUTUSAN MA NO. 45/PK/PDT.SUS/PAILIT/2016) - SOFIA ANGGRAINI (PREMISE LAW JURNAL, 2017)
The state (fiscus) as the collector of tax payable with coercion has the right to precede by law in dunning tax payable, including the tax payable of bankrupt debtors. In restructuring a bankrupt debtor’s property by the curator. Fiscus who get unsecured debt and not preferred one can file a complaint to the court The research problems are how about the position of fiscus as preffered creditor, how about the fulfillment of the principle of legal certainty of the Supreme Court’s Ruling No. 45/PK/Pdt.Sus/Pailit/2016, how about the legal consequence of fiscus after the issuance of that Supreme Court’s Ruling. The research used juridicial normative with case approach. The result of the research are the calculation of five years is calculated since the issuance of the Warrant officially. The Ruling does not fulfill legal certainty because it does not consider the implementation of KUP. The legal consequence of the Ruling is that the State suffers financial loss. Since the State has preemptive right, the preemptive right has to be used well. The judge should consider the prevailing regulations for concerete cases. The Rulling has caused the loss of the revenue of the State treasury which can actually be used for the people’s walfare. Keywords: Preemptive Right, Tax Payable